2016
DOI: 10.1212/wnl.0000000000002950
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus is associated with brain atrophy and hypometabolism in the ADNI cohort

Abstract: Objective: We investigated type 2 diabetes mellitus (T2DM) as a risk factor for brain atrophy and glucose hypometabolism in older adults with or at risk of cognitive impairment.Methods: Participants with the T2DM were identified from the Alzheimer's Disease Neuroimaging Initiative (ADNI-1/GO/2 cohorts). Analysis of covariance models were used to compare participants with and without T2DM, controlling for potential confounding factors.Results: Whole brain volume and whole brain [18 F]-fluorodeoxyglucose (FDG) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 33 publications
2
51
1
Order By: Relevance
“…On the other hand, T2DM patients with mild cognitive impairment (MCI) showed a general reduction in brain [ 18 F]-fluorodeoxyglucose (FDG) uptake in gray and white matter [22]. Insulin resistance has also been associated with a reduced cerebral glucose metabolic rate in frontal, temporal-parietal, and cingulate regions in patients with T2DM [23,24].…”
Section: A) Alterations In Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, T2DM patients with mild cognitive impairment (MCI) showed a general reduction in brain [ 18 F]-fluorodeoxyglucose (FDG) uptake in gray and white matter [22]. Insulin resistance has also been associated with a reduced cerebral glucose metabolic rate in frontal, temporal-parietal, and cingulate regions in patients with T2DM [23,24].…”
Section: A) Alterations In Glucose Metabolismmentioning
confidence: 99%
“…Interestingly, brain hypometabolism (observed by FDG uptake) is associated with an increased risk for AD and can be observed years before the dementia onset in the same brain regions affected in T2DM patients [25,26]. Thus, the reduced cerebral glucose metabolic rate observed in diabetic patients could be a predisposing factor for AD and MCI [22]. b) Vascular and structural brain abnormalities T2DM is linked to alterations in cerebral microvasculature, including amyloid angiopathy [16,27].…”
Section: A) Alterations In Glucose Metabolismmentioning
confidence: 99%
“…Functional MRI studies showed a dysfunction in glucose metabolism in patient having Alzheimer disease and also in small subcortical structures in patients with Parkinson disease. 89,90 Besides showing significantly more cognitive deficits, T1D and T2D patients display equally more behavioral alterations such as depression, related to their condition. 4,10 In fact, depression is a risk factor for developing diabetes 91 as glycemic control is affected by lifestyle (e.i.…”
Section: Diabetes Neurotransmission Cognitive Impairment and Behavimentioning
confidence: 99%
“…Many previous studies have investigated the relationship between diabetes-associated factors (such as HbA1c, diabetes status, blood glucose, cognitive function, and brain atrophy and/or metabolism), in addition to insulin resistance and cognitive impairment [ 33 , 34 , 35 ]. The current study indicates that only insulin resistance has a significant effect on the relationship between structural changes in key brain regions sensitive to insulin and cognitive deterioration.…”
Section: Discussionmentioning
confidence: 99%